Resource acquisition and reproductive strategies of tropical forest in response to the El Niño–Southern Oscillation - Detto, Matteo; Wright, S. Joseph; Calderón, Osvaldo; Muller-Landau, Helene C. (Nature communications, 2018)
The El Niño–Southern Oscillation (ENSO) is the largest source of interannual climate variability in much of the tropics. We hypothesize that tropical plants exhibit interannual variation in reproduction and resource acquisition strategies driven by ENSO that mirrors their seasonal responses. We analyze the relationship of leaf and seed fall to climate variation over 30 years in a seasonally dry tropical forest in Panama where El Niño brings warm, dry, and sunny conditions. Elevated leaf fall precedes the onset of El Niño, and elevated seed production follows, paralleling associations with dry seasons. Our results provide evidence of a shift in allocation from leafing to fruiting in response to a warming phase of ENSO. This shift may enable plants to take advantage of higher light availability, while coping with higher atmospheric water demand and lower water supply. These findings might be an indicator of adaptive strategies to optimize reproduction and resource acquisition. It has been suggested that tree phenology may be regulated by climatic oscillations. Here, Detto et al. present a 30 year tropical forest dataset that suggests leaf and fruit production is coordinated with ENSO cycles, with greater leaf fall observed prior to El Niño followed by greater seed production.